Práticas discursivas de subjetivação na literatura para a formação de professores de surdos - Mendes, Alex (2013)
This research work aims on subjectification practises presents on literature read by teachers under the process of professional education to work with deaf students in basic education in public schools. Since middle 90‟s of twentieth century in Brazil, efforts are made to maintain deaf students in regular schools. This action presupposes prepared teachers to take care and teach people who historically were apart from the school, starting from getting knowledge about characteristics and specifications about how these students learn. At this point, this research analysis begins when it takes as corpus some pedagogic literature works that aims to explain to the teacher under formation facts about deafness, starting with political and pedagogical aims that are diverse and even dissonant. The work begins with a historical approach about Inclusive Education, its definition and pedagogical/theoretical basis until it gets to the educational laws that authorise the existence of an educational modality oriented to a group that has specific characteristics of learning. Starting from this, the work goes to analysis of Foucault‟s archaeology that unravels by its categories of comprehension of enunciative function, the basic organization of discursive practises, its objects, modalities and the relations with the possible subjects that are authorized to discourse about deafness and the kind of subjects this kind of sayings intend to form. At this point, the research corpus is referred to know how these theories are worth to the analysis process. The next step, the analysis goes on the process of subjectification, spreading to the corpus the discussion of Foucault about discourse and its interdicts, the genealogy of power and the formation of subjectivities. The analysis also occupies itself with the notion of identity in nowadays, in according to the philosophical and sociological approach of Hall and under the concepts of life, politics and liquid modernity of Bauman. Finally, there is a specific analysis of subjectification practises that are possible to highlight from the anterior approaches, to demonstrate the production of educational professional subjects that have a certain notion of identity.